2001
DOI: 10.1074/jbc.m104130200
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 Plays a Critical Role in the Transcriptional Activation of the Human Cyclin-dependent Kinase Inhibitor p21 Gene by the p53 Tumor Suppressor Protein

Abstract: In the present study we present evidence for the critical role of Sp1 in the mechanism of transactivation of the human cell cycle inhibitor p21 WAF1/Cip1 (p21) gene promoter by the tumor suppressor p53 protein. We found that the distal p53-binding site of the p21 promoter acts as an enhancer on the homologous or heterologous promoters in hepatoma HepG2 cells. In transfection experiments, p53 transactivated the p21 promoter in HaCaT cells that express Sp1 but have a mutated p53 form. In contrast, p53 could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
126
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(136 citation statements)
references
References 78 publications
8
126
1
Order By: Relevance
“…This finding supports the clutch-like model, whereby transcription factors are able to displace nucleosomes, and are in competition with nucleosome binding. Finally, we find that TP53 mostly acts alone as a TF bound to its target enhancers, although previous studies had suggested cofactorship at the DNA level (Koutsodontis et al 2001;Thornborrow and Manfredi 2001). Note that non-sequence-specific cofactors (e.g., EP300) are likely to interact with TP53 at the protein level, independent of the DNA sequence, to recruit RNA polymerase and activate target gene transcription.…”
Section: Tp53 Enhancer Logicmentioning
confidence: 67%
See 2 more Smart Citations
“…This finding supports the clutch-like model, whereby transcription factors are able to displace nucleosomes, and are in competition with nucleosome binding. Finally, we find that TP53 mostly acts alone as a TF bound to its target enhancers, although previous studies had suggested cofactorship at the DNA level (Koutsodontis et al 2001;Thornborrow and Manfredi 2001). Note that non-sequence-specific cofactors (e.g., EP300) are likely to interact with TP53 at the protein level, independent of the DNA sequence, to recruit RNA polymerase and activate target gene transcription.…”
Section: Tp53 Enhancer Logicmentioning
confidence: 67%
“…This suggests that TP53 mainly functions alone, without other regulatory factors cobinding at the DNA level. This is surprising as one of the proposed mechanisms for TP53 target specificity is through the recruitment of coregulatory transcription factors (Koutsodontis et al 2001;Thornborrow and Manfredi 2001).…”
Section: Unsophisticated Tp53 Enhancer Logicmentioning
confidence: 85%
See 1 more Smart Citation
“…Because p21 is a transcriptional target of p53, it plays a crucial role in mediating growth arrest when cells are exposed to DNA-damaging agents such as doxorubicin and g-irradiation (16). Apart from p53, a variety of other factors including Sp1, p300/CBP, c-Jun, and E2F are known to activate p21 transcription (17)(18)(19)(20). Additionally, various mechanisms exist to regulate the levels of p21 protein in a cell including transcriptional regulation, epigenetic silencing, mRNA stability, and ubiquitin-dependent and ubiquitin-independent degradation of the protein (17,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The p21 gene, mainly regulated at the transcriptional level, plays a crucial role in mediating growth arrest when cells are exposed to DNA-damaging agents (7). Over-expression of p21 results in G1-, G2-, or S-phase arrest upon exposure to DNA-damaging agents (8,9). Whereas induction of p21 predominantly leads to cell cycle arrest, repression of p21 may have a variety of outcomes depending on the cellular context (10).…”
Section: Introductionmentioning
confidence: 99%